PENGARUH TINGKAT PENDIDIKAN, KREATIVITAS, PENGALAMAN KERJA TERHADAP PRODUKTIVITAS DAN PENDAPATAN TENAGA KERJA INDUSTRI KERAJINAN ANYAMAN - Mahendra, Putu Andhika; Rustariyuni, Surya Dewi (Buletin Studi Ekonomi; VOL.24.NO.1.FEBRUARI 2019, 2019)
Abstract: Effect of Levels of Education, Creativity, Work Experience on Productivity and Income of Woven Craft Industry Workers. The manufacturing industry sector has an important role in increasing national development, within two years the woven craft industry in the city of Denpasar has decreased theh number ofh workers resulting from productivity that is not optimal in meeting the targets set by the company. The purpose of this study is to analyze the effect ofh direct and indirect levels of education, creativity, work experience on labor productivity andhhincome. This research uses path analysis methods. The results of the study state thathhthe level of education, work experience hasha negative effect andhis not significant on labor productivity, while creativity has a positive and significant effect on labor productivity with a valuehof 0.338, and direct influence on education level, labor productivity has a negative effect and is not significant towards labor income , while creativity has a positive and significant effect on labor income with a value of 0.118, and work experience has a positive and significant effect on labor income with a value of 0.819. The results of testing the indirect effect state that the level of education, creativity, work experience does not have an indirect effect on income and work through labor productivity.